Genetic Analysis of H5N1 High-Pathogenicity Avian Influenza Virus following a Mass Mortality Event in Wild Geese on the Solway Firth - Craig S. Ross; Alexander M. P. Byrne; Sahar Mahmood; Saumya Thomas; Scott Reid; Lorna Freath; Larry R. Griffin; Marco Falchieri; Paul Holmes; Nick Goldsmith; Jessica M. Shaw; Alastair MacGugan; et al. (Pathogens, 2024)
The United Kingdom (UK) and Europe have seen successive outbreaks of H5N1 clade 2.3.4.4b high-pathogenicity avian influenza virus (HPAIV) since 2020 peaking in the autumn/winter periods. During the 2021/22 season, a mass die-off event of Svalbard Barnacle Geese (Branta leucopsis) was observed on the Solway Firth, a body of water on the west coast border between England and Scotland. This area is used annually by Barnacle Geese to over-winter, before returning to Svalbard to breed. Following initial identification of HPAIV in a Barnacle Goose on 8 November 2021, up to 32% of the total Barnacle Goose population may have succumbed to disease by the end of March 2022, along with other wild bird species in the area. Potential adaptation of the HPAIV to the Barnacle Goose population within this event was evaluated. Whole-genome sequencing of thirty-three HPAIV isolates from wild bird species demonstrated that there had been two distinct incursions of the virus, but the two viruses had remained genetically stable within the population, whilst viruses from infected wild birds were closely related to those from poultry cases occurring in the same region. Analysis of sera from the following year demonstrated that a high percentage (76%) of returning birds had developed antibodies to H5 AIV. This study demonstrates genetic stability of this strain of HPAIV in wild Anseriformes, and that, at the population scale, whilst there is a significant impact on survival, a high proportion of birds recover following infection.